RESILIENSI MAHASISWI ETNIS JAWA DALAM MENGHADAPI STIGMA NEGATIF MENGENAI PENDIDIKAN TINGGI DI DESA SEI MENCIRIM KECAMATAN KUTALIMBARU - Pratiwi, Annisa; Fimansyah, Wira (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2024)
This research aims to find out the negative stigma about higher education given by the Javanese ethnic community to Javanese ethnic students, find out the negative impact of the stigma about higher education obtained by Javanese ethnic students and find out the resilience efforts of Javanese ethnic students in facing the negative stigma of society regarding education in Sei Mencirim Village, Kutalimbaru District. The method used in this research is a qualitative research method with a descriptive approach. Data collection techniques were obtained through non-participant observation, interviews and documentation using data analysis techniques in the form of data collection, data reduction, data presentation and conclusion drawing. The results of the study indicate that the stigma regarding higher education given by the Javanese ethnic community to Javanese ethnic female students is closely bound by Javanese cultural values that Javanese women revolve around the 3M area macak (decorate themselves), manak (give birth), masak (in the kitchen) or kitchen, well, mattress the stigma has a different negative impact on each female student including negative cognitive impacts, physiological impacts, emotional impacts and behavioral impacts. The existence of resilience efforts owned by female students succeeded in making them rise from the negative impact, the efforts they made were different, including students making positive affirmations, improving the quality of worship, and occupying themselves with positive activities, so that from these efforts some students still continued their studies and some of them had completed their studies and succeeded in achieving the goals they craved